الادارة المؤقتة للاموال الموضوعة تحت الحراسة - حسن حيدر فليح; حنون نسرين غانم (Journal of Legal Sciences, 2019)
The interim administration is an application of the idea of ​​management required by certain circumstances, which are necessary and urgent, and most laws, especially the laws we have compared (the French Civil Code and the Egyptian civil law and the Iraqi civil law) did not regulate the idea of ​​interim administration accurately, This idea is interrelated, but this idea is highlighted whenever a temporary administrator is needed. It is often necessary to maintain a financial or financial burden that is impossible for the owner to manage his own money for one reason or another, the appointment of a temporary manager who manages these funds, we find the legislator resort in such a case to appoint a manager to temporarily save and manage the funds, The appointment of the interim director in the event that the legislator does not provide for his appointment. In the idea of ​​interim administration, we find a wide application of the idea of ​​the work of the Department as the need arises to put money under guard when there is a dispute, claiming the existence or right of two or more people, and the task of the guard is to keep the thing and maintain and manage until the dispute is resolved, The reason for this is the right of the person to prove it to him. The reason for the guard may be the signing of a reservation on the matter. A guard is needed until the execution procedures are completed. The guard may be in agreement with the contestants. And thus require the need to search divided by two requirements we allocate the first requirement of the concept of custody and types, and we meet the second requirement for the work of management issued by the guard.